MEANING AND SYMBOLIC CULTURE OF THE SEEDAH LAUT TRADITION IN KARANG BENDA VILLAGE, CILACAP DISTRICT IN 2020 - Nur Fajar Rizkia; Siswanta (CV. Fahr Publishing, 2023)
The Meaning and Symbolism of the Sea Alms Traditional Culture in Karang Benda Village, Cilacap Regency in 2020. Thesis. Yogyakarta Faculty of Teaching and Education, Yogyakarta PGRI University. This study aims to examine the historical origins of the sea alms ceremony in Cilacap district, find out the implementation of the alms alms tradition celebration and explain the symbolic meaning and exemplary value of the sea alms ceremony in Cilacap district. This research was conducted at Teluk Penyu Beach, Cilacap Village, Cilacap Regency. Data collection techniques in the form of interviews, observations and documents or archives in the period 2010-2019. Interviews were conducted with members of the Cilacap City Fishermen's Association, fishermen, and Cilacap City traditional leaders. The results of the study explain that 1) the sea alms ceremony in Cilacap Regency is held once a year in the month of Suro which coincides with Tuesday Kliwon or Friday Kliwon, 2) This traditional ceremony has a religious meaning, namely as a manifestation of gratitude for the catch of fish and a prayer request for safety and abundance of fish catches in the following year, 3) This traditional ceremony also contains symbolic meanings such as tumpeng as a symbol of divinity.